State dependence in Swedish social assistance - Daniela Andrén; Thomas Andrén (Örebro University School of Business, 2013)
Although the economic integration of immigrants has been the subject of a large number of studies, the research on the effect of intermarriage on immigrants' economic integration/assimilation is scarce and has no equivalence in the literature on the receipt of social assistance. This study fills this gap in the literature by estimating the structural state dependence in social assistance in Sweden during 1990-1999 by different types of households, which were grouped by the country of birth of the sampled individual and his/her partner. Using a dynamic discrete choice model that controls for unobserved heterogeneity and the initial conditions problem, we find that state dependence in Swedish social assistance was relatively strong during 1990-1999, and differed extensively across different household types. Although Swedish-born partners who separated are one of the groups with the lowest receipt of social assistance (i.e., 1.08-1.76%), these individuals exhibit the highest state dependence (24.4 percentage points). Foreign-born singles have almost the same value for the state dependence, but these individuals also have the highest receipt of social assistance (18.47%). Surprisingly, the group with the lowest receipt of social assistance (0.27-3.06%) and the lowest state dependence (4.7 percentage points) are the foreign-born women living together with a Swedish-born man.
Keywords: I30; I38; J18; 330; social assistance; state dependence; unobserved heterogeneity; initial conditions; dynamic probit model; GHK simulator